2020
DOI: 10.1097/icl.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ocular Demodex Colonization on Schirmer test and OSDI Scores in Newly Diagnosed Dry Eye Patients

Abstract: Objective: To determine whether ocular Demodex colonization results in differences in Schirmer test scores and Ocular Surface Disease Index (OSDI) questionnaire values in individuals with dry eye disease (DED) diagnosed for the first time. Method: Eighty-eight adults aged 40 to 68 years who were admitted to Ophthalmology outpatient clinic for routine ophthalmological examination or presbyopia examination and diagnosed with DED for the first time and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…We wondered whether young patients are more susceptible to corneal involvement than elderly patients. However, other studies that mostly included elderly patients have shown that the most common clinical features are MGD and eye dryness with predominantly D. folliculorum (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…We wondered whether young patients are more susceptible to corneal involvement than elderly patients. However, other studies that mostly included elderly patients have shown that the most common clinical features are MGD and eye dryness with predominantly D. folliculorum (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…84 Li et al 65 reported ocular Demodex to be less prevalent in people with aqueous-deficient dry eye disease, diagnosed using a tear clearance diagnostic test, relative to those without the condition. However, two studies have found no relationship between ocular Demodex density and Schirmer test scores (Lee et al 29 ; Chanlalit et al 33 ) and, in contrast, Ayyildiz et al 54 recently reported that ocular Demodex colonisation was associated with significantly poorer Schirmer test scores. These apparently divergent findings may relate to differences in the study populations, including the duration and severity of dry eye disease, the criteria used to diagnose the condition and the method(s) used to define the presence of Demodex.…”
Section: General Populationmentioning
confidence: 99%
“…Although Demodex infestation can present with little to no symptoms, there are co-morbidities that have been associated with its presence, such as blepharitis, 49,[72][73][74] meibomian gland dysfunction (MGD), 69,72,75,76 keratitis, 72,77 blepharokeratoconjunctivitis, 56 chalazion, 55,72,78 dry eye, 79 and pterygium. 80 The risk of Demodex in patients with blepharitis is 2.5-fold, while the risk in rosacea patients is threefold higher than in the general population.…”
Section: Demodex and Eye Diseasementioning
confidence: 99%
“…94,101 Others have shown that the Schirmer test is reduced and the OSDI score is greater in dry eye patients with Demodex. 79 Other studies have used corneal and conjunctival staining, osmolarity, meibum expression and matrix metalloproteinas-9 levels, as outcome measures with conflicting relationships to demodicosis. 37,56,65,112,125,136,151,152 Clearly, there are no well-established correlations between Demodex and ocular signs, which mirrors the challenges encountered for studies in dry eye disease.…”
Section: Future Considerationsmentioning
confidence: 99%